2010
DOI: 10.1007/s00125-010-1875-9
|View full text |Cite
|
Sign up to set email alerts
|

Leisure-time physical activity and type 2 diabetes during a 28 year follow-up in twins

Abstract: Aims/hypothesis The study aimed to investigate whether baseline physical activity protects against the occurrence of type 2 diabetes during a 28 year follow-up, after controlling for childhood environment and genetic predisposition. Methods At baseline in 1975 same-sex twin pairs born in Finland before 1958 were sent a questionnaire including questions on physical activity. The participants (20,487 individuals, including 8,182 complete twin pairs) were divided into quintiles by leisure-time physical activity m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 38 publications
(50 reference statements)
5
28
0
1
Order By: Relevance
“…We estimated the shared genetic influence of BMI and type 2 diabetes to be 19%, which indicates that these traits are, in part, influenced by the same genes. This confirms findings based on Finnish, Indian and Australian twins [6][7][8]. There are some potential pleiotropic genes, including the FTO gene, which has been linked to BMI as well as type 2 diabetes [10].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We estimated the shared genetic influence of BMI and type 2 diabetes to be 19%, which indicates that these traits are, in part, influenced by the same genes. This confirms findings based on Finnish, Indian and Australian twins [6][7][8]. There are some potential pleiotropic genes, including the FTO gene, which has been linked to BMI as well as type 2 diabetes [10].…”
Section: Discussionsupporting
confidence: 88%
“…This suggests that the strong genetic influence of physical activity (57%) is related to genes that are essentially different from those related to type 2 diabetes. To the best of our knowledge, the shared genetic component of physical activity and type 2 diabetes has not been estimated previously, but these findings are supported by a report from the Finnish Twin Cohort [6].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…30 In line with this, a 28-year follow-up of 8182 Finnish twin pairs showed significant reductions (HR 0.54; 95% CI 0.37 --0.78) in the risk for Type 2 diabetes in twin pair members that had been physically active during the whole of their adult lives compared with consistently inactive co-twins. 32 Intensive substudies of these physical activity discordant twins further revealed that although the physically inactive (79.5 ± 18.4 kg) and active twins (72.9 ± 11.9 kg) had only small differences in body weight, the inactive twins had 170% more liver fat and 54% more intramuscular fat than the active twins. 33 Thus, the value of physical activity should not be judged only by its' effects on body weight.…”
Section: Development Of Obesitymentioning
confidence: 96%
“…It may also be noted that the categorization of inactive and active participants was not completely consistent with current physical activity recommendations [5,6] due to the limitations of the questionnaire. On the other hand, among the predominantly obese population at high risk of type 2 diabetes (for whom any increase in PAL is of great benefit), it seems reasonable to use lower cut-off point for categorizing the participants' PAL [33]. A general point to note is that the results of this study are based on the classification defined in the Methods section and should be interpreted accordingly.…”
Section: Determinants Of Overestimation Of Palmentioning
confidence: 95%